India's Economic Crisis: The Way Ahead - Bimal Jalan; JALAN (Bimal) (Delhi Oxford University Press, 1991)
As a result of changes in the international political arena as well as upheaval in India's own sphere, many in India are scrutinizing their economic crisis. Jalan argues that centralized planning and direct state control were inevitable--even desirable--during post-Independence through the 1960s. Now, the inadequacies of this system are finally addressed.
Keywords: Economics; Economic Policy; Finance Public